Characteristics of the morphological status of children of junior school age with auditory derivation - Dus, Sergiy (Journal of Education, Health and Sport, 2017)
Topicality. Physical development of a child is a complex process, based on an individual genetic program, which is implemented in certain, but not always optimal conditions of the environment. Deviations in physical development are associated with genetic factors, nutritional status, chronic diseases, motor activity, climate, habitat, conditions of education and other environmental influences. Objectives of the study: To systematize the results of practical experience on the peculiarities of the morphological status of elementary school children with hearing impairment in the process of physical education. Research results. Specialists in the field of adaptive physical education note that practically all children of junior school age with sensory impairments have problems of disharmonious physical development, formation and improvement of motor functions. Analysis of literary sources indicates the relevance of scientific developments on the problem of harmonious development of elementary school children with hearing impairments in the process of physical education, which is determined, first of all, by a significant level of prevalence of this nosology. Conclusions The decrease in the frequency of pathology of sensory systems in the coming years is not expected, because the main factors that cause the loss of vision and hearing can not be eliminated in a short period. In this regard, constant development and improvement of methods of comprehensive assistance to children with deprivation of sensory systems is necessary.